Comparison of allograft-prosthetic composite reconstruction and modular prosthetic replacement in proximal femur bone tumors: Functional assessment by gait analysis in 20 patients. (1st January 2013) - Benedetti, Maria Grazia; Bonatti, Enrica; Malfitano, Calogero; Donati, Davide
Abstract : Background and purpose The methods of reconstruction for proximal femur bone tumors that are used most often include modular prosthetic replacement and allograft-prosthesis composite reconstruction. In modular prostheses, the abductors are detached from the insertion and then reinserted into the implant, and the iliopsoas is detached and left free. In the allograft-prosthesis composite, the detached tendons are fixated to the graft. We assessed whether the latter procedure provides functional advantages regarding gait. Patients and methods We studied 2 groups of 10 patients, each with prosthetic reconstruction of the proximal femur either with modular prosthetic replacement or with allograft-prosthesis composite. Functional performance was analyzed by gait analysis 2.5–10 years after surgery. At that time, all the patients had good function according to the Musculoskeletal Society score. Results Walking speed was reduced in all patients, and especially in patients with modular prosthetic replacement. Different hip extension patterns during late stance were found in the 2 groups. Surface EMG showed a typical prolonged muscle co-contraction pattern during gait, which was more evident in modular prosthetic patients. Interpretation Although both procedures provided good functional outcome in the long-term follow-up, gait analysis revealed mechanical changes during gait that were probably related to the muscle reinsertion procedure. Direct fixation of the muscles to the bone graft appeared to result in a more efficient muscular recovery.